Large scale seabed processes in a deep cool water carbonate ramp system: A case study of the Great Australian Bight. (March 2021) - Talukder, Asrar; Ross, Andrew S.; Trefry, Christine; Pickard, April; Tam, Thomas
Abstract: Among all the modern cool water carbonate margins in the world, the Great Australian Bight (GAB) presents several unique characteristics: a near complete absence of terrigenous input, highly energetic swell conditions producing vigorous off-shelf sedimentary transport to the upper continental slope, and overall high-sedimentation rates during the Pleistocene. All these conditions promoted biota and facies that are more typical of a highly productive carbonate margin. High-resolution bathymetric data collected from marine voyages between 2015 and 2017 revealed that the continental slopes of the central GAB are characterised by numerous channels and canyons as well as a large number of sedimentary mass-wasting features including kilometre scale submarine landslides and slumps. The morphometric and structural analysis of these seabed features across the continental slopes suggest that the three key controlling factors are: deep-rooted faults breaching the seabed, increasing slope gradient at the beginning of the lower continental slope, and channel wall erosion. Pulses of rapid sedimentary accumulation on the upper continental slopes, as well as differential uplift and subsidence combined with sea-level changes, appear to be the main trigger mechanisms for mass wasting. The GAB is the largest cool-water carbonate ramp system in the world. As such, the scale of sedimentary erosion and transport through channels and canyons caused by mass wasting identified in this work represents a major mechanism of carbon transfer to the deep oceans. Whilst high carbonate sedimentation during the Pleistocene in the GAB could be an important CO2 sink in the global ocean, high sedimentation on the outer shelf and continental slope could also increase mass wasting which could act as an effective mechanism for carbon transfer to the deep oceans. However, continental slopes in the Great Australian Bight have, until recently, remained poorly studied. Highlights: Mass wasting features and submarine canyons are very common across the central GAB. There are three main factors that appear to control the location of mass failures; deep faults, increased slope gradient and canyon wall erosions. Trigger mechanisms include differential uplift/subsidence, high Pleistocene sedimentation and sea level changes. Regional seismic studies most likely underestimated the Cenozoic sedimentary rates. The Mass wasting identified in this study have transferred significant volumes of carbonate sediments to deep sea, representing a major source of carbon sink in the global ocean.